(untitled) (Bangladesh Journal of Zoology, 2013)
The effects of the pesticide Abate on the ovary of the cat fish Heteropneustes fossilis (Bloch.) was studied by observing the vitellogenesis of the fish. The LC50 of Abate (0.64 ppm) after 24, 48, 72 and 96 hours of exposure to the fish was determined to be 14.3, 10.0, 6.61 and 5.13 ppm, respectively. The glycogen contents in the normal fish were lowest (6.0 mg/g) and highest (21.96 mg/g) in December and August, respectively; the protein contents were lowest (102.65 mg/g) in August and highest (424.17 mg/g) in December; whereas, the cholesterol was the lowest (9.32 mg/g) in November and highest (15.76 mg/g) in August. In the Abate treated fish, the lowest and highest contents of biochemicals were: 3.58 and 17.10 mg/g of glycogen in December and August, respectively; 80.44 and 378.34 mg/g of protein in December and August, respectively; and 7.15 and 12.92 mg/g of cholesterol in December and August respectively. The results show that the pesticide Abate has the potentiality to alter the vitellogenesis of the fish. DOI: http://dx.doi.org/10.3329/bjz.v40i2.14314 Bangladesh J. Zool. 40(2): 207-212, 2012